Growth, yield and post harvest quality of late season varieties of cauliflower at Rampur, Chitwan - Giri, H. N. (Journal of Agriculture and Forestry University, 2020)
An experiment was done to evaluate eleven late season cauliflower varieties at Rampur, Chitwan, Nepal during November 2017 to March, 2018. All the tested varieties were introduced from USA, Europe, and India viz. Amazing, Artica, Freedom, Ravella, Titan, Bishop, Casper, Indam 9803, and NS 106 while two varieties; Snowmystique and Snowball 16 were from Nepal. The experiment was set by using Randomized Complete Block Design (RCBD) with an arrangement of each treatment replicated for four times. The main objective of this study was to identify the short duration late season varieties of cauliflower to be adapted to high temperature condition during late winter. Parameters considered to evaluate the varieties included- plant height, leaf length, canopy diameter, curd height, curd diameter, yield, along with postharvest parameters, such as Total soluble solid (TSS), Titrable acidity (TA), pH, and Vitamin C content. Similarly, 50% curd initiation and curd maturity of the cauliflower was also measured to find the crop growth period. The highest plant height, leaf length and canopy diameter was mostly produced by Titan, Snow mystique, and NS 106 while the lowest plant height, leaf length and canopy diameter was produced by Snowball 16 and Amazing. Similarly, significantly shorter period for 50% curd initiation of 68 days was observed in NS 106 and shorter period for 50% curd maturation of 78 days was recorded in Freedom compared to the rest of the treatments. Significantly largest curd height and diameter was measured for NS 106. Similarly, significantly higher curd yield of 52.3 t/ha was produced by Bishop, but it was statistically similar (p>0.05) to NS 106 (51.1 t/ha). Likewise, significantly higher TSS of 5.4 ºBrix and Vitamin C content of 55 mg/100 g was produced by Snowball 16 and Bishop, respectively. Thus, the probable varieties that could be considered best for late winter could be Bishop, NS 106, Snowmystique, Artica, Freedom, Titan, and Amazing that may comparatively better adapt to the high temperature condition.